2009
DOI: 10.1002/gps.2272
|View full text |Cite
|
Sign up to set email alerts
|

Mental capacity to consent to treatment and admission decisions in older adult psychiatric inpatients

Abstract: Patients can have capacity to make decisions in one area but not in others. Many people are admitted and treated in a way that is contrary to the human rights legislation. The new Deprivation of Liberty Safeguards in England and Wales are likely to apply to a significant proportion of older inpatients. Most people wanted doctors to make treatment and admission decisions and very few wanted their family to make decisions on their behalf.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 17 publications
1
34
0
Order By: Relevance
“…Using cutoffs derived from an earlier study, they concluded that the proportion of subjects impaired on at least one competence-related function was 20% for the depressed group, 54% for those with schizophrenia, and 68% for those with AD. Indeed, when decisional competence was assessed among 99 newly admitted elderly psychiatric patients in a British study using the MacCAT-T, a clinical diagnosis of any type of dementia was the strongest predictor of incapacity, followed by insight and MMSE score [18]. Of interest, in the German study, attending physicians tended to be less sensitive than the MacCAT-T in detecting impairment.…”
Section: Consent To Treatmentmentioning
confidence: 98%
See 3 more Smart Citations
“…Using cutoffs derived from an earlier study, they concluded that the proportion of subjects impaired on at least one competence-related function was 20% for the depressed group, 54% for those with schizophrenia, and 68% for those with AD. Indeed, when decisional competence was assessed among 99 newly admitted elderly psychiatric patients in a British study using the MacCAT-T, a clinical diagnosis of any type of dementia was the strongest predictor of incapacity, followed by insight and MMSE score [18]. Of interest, in the German study, attending physicians tended to be less sensitive than the MacCAT-T in detecting impairment.…”
Section: Consent To Treatmentmentioning
confidence: 98%
“…Perhaps expectedly given the level of cognitive impairment, the group showed extremely poor performance on understanding and appreciation; reasoning could not even be assessed in subjects with this degree of disability. Lai et al [36] developed a measure of capacity to make decisions about everyday life and tested it in 39 patients with diagnoses ranging from MCI to moderate dementia (MMSE score, [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30]. Performance showed moderate to strong correlations with MMSE and MacCAT-T scores.…”
Section: Other Decisional Tasksmentioning
confidence: 99%
See 2 more Smart Citations
“…of Health, 2005); for example, equating the presence of dementia with a lack of capacity. Similarly, whilst people with severe dementia may have more impaired capacity overall (for example, Maxmin et al 2009), nonetheless, as they can retain capacity in particular areas, their 'decision-specific' capacity must be assessed before making decisions on their behalf. The Act covers health care, personal welfare, financial and property decisions (for example, Sections 17 and 18).…”
Section: Introductionmentioning
confidence: 99%